The harder we fall - Esguerra, Mina V. (Mandaluyong City Anvil, 2015)
She knows it won't last...Nicholas is unlike anyone Daria has ever dated, and yet he hasn't left her mind since she got her hands on the 23-year-old rugby player when he took a tumble during a game.But they aren't even really dating; a fast fling is all they have time for. He's heading to Japan to play pro and is only in town to tie loose ends. She's graduating in three weeks, and is only covering his struggling rugby club to win an internship spot in a documentary that will start filming in Europe.Getting what they want means they don't get to stay together. But that doesn't mean they can't have fun -- as long as they don't fall hard.
Keywords: Romance fiction, Philippine (English).; Philippine Fiction (English).